Working together or separately? The role of identity and cultural self‐construal in well‐being among Japanese youth. Issue 4 (21st November 2016) - Sugimura, Kazumi; Nakama, Reiko; Mizokami, Shinichi; Hatano, Kai; Tsuzuki, Manabu; Schwartz, Seth J.
Abstract : Young people develop a sense of personal identity during the transition to adulthood, a time when individuals choose and adhere to a specific set of goals, values, and beliefs. In addition, in many contemporary Asian societies, youth are expected to acquire and balance traditional and Western cultural views of the self — that is, independent and interdependent self‐construal. To understand the relationships between the personal and cultural facets of the transition to adulthood, this study examined (a) associations between personal identity and well‐being and (b) the possible moderating role of cultural self‐construal (independence and interdependence) in this link. These hypotheses were tested in a sample of 520 Japanese university students (52.6% female). The results indicated that personal identity predicted each dimension of well‐being, suggesting that the importance of personal identity in promoting youth's well‐being can be understood as a universal phenomenon. Moreover, because the moderating role of self‐construal in the links between identity and well‐being was found to be limited, personal identity can be viewed as operating separately from self‐construal in well‐being to a large extent. Implications and suggestions for future research are discussed.